Accidental High Voltage Electrocution: a Case Report - Kishore, Sh K; Rani, S; Marigoudar, R M; Balaraj, M B (International Journal of Medical Toxicology and Forensic Medicine, 2016)
Background: Without electricity, mankind wouldn’t have progressed to the heights we are at now. As much as electricity is helpful, being careless with it can be fatal. The passage of electric current through the body produces wide range of effects, varying from insignificant localised spasm, little or no contact burns, fatality with little or no burns or extreme severe burning. Case Report: This case report discusses the injuries sustained by a young adult, due to accidental contact with high tension wire. Conclusion: This paper also highlights safety rules pertaining to high voltage cables.